Bannayan–Riley–Ruvalcaba Syndrome with Progressive Spinal Epidural Lipomatosis - Toelle, Sandra; Poretti, Andrea; Scheer, Ianina; Huisman, Thierry; Boltshauser, Eugen (Neuropediatrics, 2012)
We present a case study of an 11-year-old boy with Bannayan–Riley–Ruvalcaba syndrome (BRRS) with macrocephaly, lipomatosis, and penile freckles. BRRS was confirmed by a germline mutation in the phosphatase and tensin homolog (PTEN) gene. Repeated spinal imaging demonstrated an extensive progressive spinal epidural lipomatosis, compressing and dislocating the dural sac, so far without neurological deficits. Patients with BRRS are probably a risk for progressive spinal epidural lipomatosis and should be carefully monitored by neurological examinations and eventually neuroimaging follow-up studies.
Keywords: Bannayan–Riley–Ruvalcaba syndrome; spinal epidural lipomatosis; PTEN